Pendampingan Pengukuran Arah Kiblat di Musollah Kafe Ruumi Mengunakan Metode Astronomi - Alamsyah, Alamsyah; Risal, Risal; Rufaida, Erty Rospyana (Yayasan Abdurrauf Cendekia Nusantara, 2024)
The determination of the Qibla direction is a crucial aspect of Islamic worship, particularly in the performance of prayer. In Indonesia, issues regarding inaccurate Qibla directions in mosques and prayer rooms have been identified, especially following the issuance of fatwas by the Indonesian Ulema Council (MUI) in 2010. This study aims to assist in measuring and verifying the accuracy of the Qibla direction at the Musollah of Ruumi Café in Makassar, Indonesia, using astronomical methods. Measurements were conducted from August 15 to August 22, 2024, using the Istiwa'aini tool. The results indicated a deviation of 12 degrees from the correct Qibla direction, with a measured azimuth difference of 342°37'03.94